Frequency dependence of surface acoustic wave swimming. Issue 155 (19th June 2019) - Pouya, C.; Hoggard, K.; Gossage, S. H.; Peter, H. R.; Poole, T.; Nash, G. R.
Abstract : Surface acoustic waves (SAWs) are elastic waves that can be excited directly on the surface of piezoelectric crystals using a transducer, leading to their exploitation for numerous technological applications, including for example microfluidics. Recently, the concept of SAW streaming, which underpins SAW microfluidics, was extended to make the first experimental demonstration of 'SAW swimming', where instead of moving water droplets on the surface of a device, SAWs are used as a propulsion mechanism. Using theoretical analysis and experiments, we show that the SAW swimming force can be controlled directly by changing the SAW frequency, due to attenuation and changing force distributions within each SAW streaming jet. Additionally, an optimum frequency exists which generates a maximum SAW swimming force. The SAW frequency can therefore be used to control the efficiency and forward force of these SAW swimming devices. The SAW swimming propulsion mechanism also mimics that used by many microorganisms, where propulsion is produced by a cyclic distortion of the body shape. This improved understanding of SAW swimming provides a test-bed for exploring the science of microorganism swimming, and could bring new insight to the evolutionary significance for the length and beating frequency of swimming microbial flagella.